Metal–Semiconductor Phase Twinned Hierarchical MoS2 Nanowires with Expanded Interlayers for Sodium‐Ion Batteries with Ultralong Cycle Life. Issue 3 (18th December 2019) - Ye, Wei; Wu, Fangfang; Shi, Nianxiang; Zhou, Han; Chi, Qianqian; Chen, Weihua; Du, Shiyu; Gao, Peng; Li, Haibo; Xiong, Shenglin
Abstract: Sodium‐ion batteries (SIBs) are considered a prospective candidate for large‐scale energy storage due to the merits of abundant sodium resources and low cost. However, a lack of suitable advanced anode materials has hindered further applications. Herein, metal–semiconductor mixed phase twinned hierarchical (MPTH) MoS2 nanowires with an expanded interlayer (9.63 Å) are engineered and prepared using MoO3 nanobelts as a self‐sacrificed template in the presence of a trace amount of (NH4 )6 Mo7 O24 ·4H2 O as initiator. The greatly expanded interlayer spacing accelerates Na + insertion/extraction kinetics, and the metal–semiconductor mixed phase enhances electron transfer ability and stabilizes electrode structure during cycling. Benefiting from the structural merits, the MPTH MoS2 electrode delivers high reversible capacities of 200 mAh g −1 at 0.1 A g −1 for 200 cycles and 154 mAh g −1 at 1 A g −1 for 2450 cycles in the voltage range of 0.4–3.0 V. Strikingly, the electrode maintains 6500 cycles at a current density of 2 A g −1, corresponding to a capacity retention of 82.8% of the 2nd cycle, overwhelming the all reported MoS2 cycling results. This study provides an alternative strategy to boost SIB cycling performance in terms of reversible capacity by virtue of interlayer expansion and structure stability. Abstract : The synthesis of metal–semiconductor phase twinned hierarchical MoS2 nanowires with expanded interlayers of 9.63 Å (mixed phase twinned hierarchical MoS2 nanowires) using MoO3 nanobelts as a self‐sacrificed template results in a high reversible capacity, unprecedented cycling life, and excellent rate capability as anode materials for sodium‐ion batteries due to their expanded interlayers, enhanced electronic conductivity, and structure stability.